Streptomyces sp. Strain SRH22: A Potential Bioremediation Agent for Glyphosate-Contaminated Agricultural Soils: 10.32526/ennrj/21/20230181 - Rebai, Hadjer; Sholkamy, Essam Nageh; Alharbi, Reem Mohammed; Abdel-Raouf, Neveen; Boufercha, Oumeima; Castro, Paula; Boudemagh, Allaoueddine (Environment and Natural Resources Journal, 2023)
Glyphosate, also known as N-phosphonomethylglycine, is the herbicide that is widely used across the globe. As there are concerns over its potential toxicity to non-target soil species, there is a growing interest in identifying glyphosate-degrading microorganisms in soil. Biodegradation, by actinobacteria, is a very promising approach to eliminate this pesticide from contaminated environments. The present work isolated and identified actinobacteria capable of degrading glyphosate from Saharan agriculture, as well as determined how the application of this herbicide affects the abundance of actinobacteria present in soil. It was observed that the use of glyphosate led to an increased abundance of actinobacteria in the soil compared to the untreated soil. Among this population, an actinobacterial strain was isolated from glyphosate contaminated soil by the enrichment method, and was identified to possess the greatest capability to degrade glyphosate at 50 mg/L. The identification of this strain was achieved through a combination of cultural, morphological, biochemical, and molecular techniques. This included the use of 16S rDNA sequencing, leading to its successful classification as Streptomyces sp. strain SRH22. This strain was assigned the accession number OQ302556 by the National Center for Biotechnology Information (NCBI). A rapid, sensitive, and straightforward spectrophotometric technique was employed for the quantification of glyphosate. Results showed that the optimal biodegradation (90.2%) was obtained under a temperature of 30 degrees, a PH of 7.2, and an inoculum volume of 4% timed over six days. This work shows that the Streptomyces SRH22 presents good potentiality to be used as a bioremediation agent for agricultural soils in the Algerian Sahara.